THE DEAD SPEAK: BIG DATA AND DIGITALLY MEDIATED DEATH - Grandinetti, Justin; DeAtley, Tyler; Bruinsma, Jeffery (AoIR Selected Papers of Internet Research, 2020)
In the following panel, we add to scholarly challenges regarding the binary distinction between life and death by examining new strategies of making productive the data of the dead. Digital media and tactics of big data collection, storage, and processing blur the boundaries of human lifecycles, allowing the individual to exist as a productive part of sociotechnical apparatuses long after their corporeal demise. Specifically, our presentations on digital data and death focus on the topics of subjectivation, consent and privacy, and commodification. Reanimator: Haunted Data, Streaming Media, and Subjectivity examines the process of subjectivation taking into account the haunted data and digital afterlives of streaming media. Here, the living and bounded subject is challenged by compositions of big data, platforms, infrastructures, and algorithms that offer the possibility of a productive sociotechnical economic subject unbounded from the human body. Grief by the Byte: Constructions of Data Consent, Privacy, and Stability in Griefbots interrogates the data practices and ethics related to the creation of chatbots from the data of deceased individuals. While “griefbots” are framed as helpful to those grieving a lost loved one, there remain questions about consent and privacy that accompany these interactions. Finally, What is Dead May Never Die: The Commodification of Death in Social Media studies how user data maintains economic value after death via networks designed to surveil, collect, and commodify the immaterial labor of the dead. These practices enable a possible economic future largely influenced by the data of the dead.